1996
DOI: 10.1007/bf01982692
|View full text |Cite
|
Sign up to set email alerts
|

Some problems concerning the evaluation of non-isothermal kinetic parameters

Abstract: The validity of isoeonversional methods used to evaluate the activation energy is discussed. The authors have shown that the Flynn-Wall-Ozawa and Friedman methods give results that agree with each other only if the activation energy does not change with the degree of conversion. A criterion for the reaction mechanism as expressed by the differential conversion function is suggested too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…According to the results reported by these workers, 15,16 the difference in the activation energies determined by the integral and differential methods does not generally exceed 10%. Nevertheless, for the process of the thermal dehydration of calcium oxalate monohydrate, Budrugeac et al 17 have found that the integral method gives rise to E α values that may deviate from the values obtained by the differential method by as much as 20%. Although this value seems to be more extreme than typical, we cannot deny the fact that the systematic error of the integral method should necessarily increase with increasing the relative magnitude of the variation in E α .…”
Section: Integral Isoconversional Methodsmentioning
confidence: 97%
“…According to the results reported by these workers, 15,16 the difference in the activation energies determined by the integral and differential methods does not generally exceed 10%. Nevertheless, for the process of the thermal dehydration of calcium oxalate monohydrate, Budrugeac et al 17 have found that the integral method gives rise to E α values that may deviate from the values obtained by the differential method by as much as 20%. Although this value seems to be more extreme than typical, we cannot deny the fact that the systematic error of the integral method should necessarily increase with increasing the relative magnitude of the variation in E α .…”
Section: Integral Isoconversional Methodsmentioning
confidence: 97%
“…(11) and (13). Data provided by Budrugeac et al [169] for the dehydration of calcium oxalate indicates that E a values obtained from integral methods can deviate by up to 21% from values determined by differential methods. In response, Vyazovkin [103] provided a modification for the V isoconversional method that accounts for the variation in apparent activation energy with increasing˛.…”
Section: Comparative Evaluation Of Integral and Differential Isoconvementioning
confidence: 97%
“…The supposition of constant E a and A values is only possible when the Arrhenius parameters are independent of the extent of reaction [140]. When E a depends on˛, however, it was found that the use of integral isoconversional methods can lead to systematic errors [139,140,169,170]. Li et al [139,171] found that values of E a are consistently overestimated using integral isoconversional methods versus those evaluated using Friedman's differential isoconversional method because of error introduced by the truncation of the additional higher-order terms in Doyle's approximations, given by Eqs.…”
Section: Comparative Evaluation Of Integral and Differential Isoconvementioning
confidence: 99%
“…For such cases a r value lower than r max could correspond to the true kinetic model. To determine the analytical form of f (α), in a previous paper [6] we suggested the criterion according to which the true analytical form of the conversion function corresponds to the activation energy determined from a single α = α(T ) curve that equals the activation energy obtained by means of isoconversional methods. By applying this criterion for the analyzed data, f (α) = 1 − α was obtained.…”
Section: Simulated Tg Curves For a Single Reactionmentioning
confidence: 99%